2014
DOI: 10.2485/jhtb.23.371
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Bank System for Bone Regeneration - Safety Report -

Abstract: The use of auto-tooth bone grafts fabricated from patients' own extracted teeth has become possible due to the development of tooth banking procedures. The Korea Tooth Bank (KTB), established in Seoul in 2009, is one such tooth-banking facility that can procure and store teeth, and then process them into bone graft substitutes. Another is the Hospital Tooth Bank (HTB) at Seoul National University Bundang Hospital (SNUBH), established in 2010 for performing storage and grafting of auto-tooth bone grafts based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The incidence of inflammatory responses, such as swelling at the early postoperative stage, was negligible and did not have any influences on bone formation despite some cases showing the occurrence of dehiscence. As reported previously 17) , these cases of dehiscence healed spontaneously, most likely due to the Type I collagenous nature of allogenic DDM (Table 2).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The incidence of inflammatory responses, such as swelling at the early postoperative stage, was negligible and did not have any influences on bone formation despite some cases showing the occurrence of dehiscence. As reported previously 17) , these cases of dehiscence healed spontaneously, most likely due to the Type I collagenous nature of allogenic DDM (Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…The dentin powder was washed with distilled water; subsequently, it was freeze-dried for 3-5 hours and was sterilized (Korea Patent Number 10-1062381). The demineralized dentin powder was kept at room temperature 17) .…”
Section: Fabrication Of Allogenic Ddmmentioning
confidence: 99%
“…Allogenic and autogenous DDMs were both derived according to the patented (Korea Patent Number: 10-1062381) method described by Kim et al 4) . Briefly, DDM powder was procured by pulverizing extracted root dentin to particles 0.3-0.8 mm in diameter, after removing the attached soft tissue and pulp.…”
Section: Fabrication Of Allogenic and Autogenous Ddmmentioning
confidence: 99%
“…After removal of the inorganic portion (demineralization), the remaining matrix could be defined as acid-insoluble collagen to which various other proteins are bound 3) . Histologically, dentin matrix consists of tubules 1-3 μm in diameter (dentinal tubules), which provide nanopore spaces that increase the surface contact area and can accommodate the rhBMP-2 solution, thereby increasing the capacity of dentin to function as an effective scaff old/carrier for rhBMP-2 [4][5][6] . With respect to using DDM as an rhBMP-2 carrier, Ike et al reported in 1998 that exogenous rhBMP-2 adsorbed into pulverized root partially demineralized dentin matrix (PDM) proved to be as osteoinductive as autogenous bone graft 7) .…”
mentioning
confidence: 99%
“…In addition, the geometrical similarity of ABTB to the alveolar bone has major advantages required in threedimensional scaffolds because ABTB outcontours the alveolar bone before extraction, which is needed for the site of future implants [11][12][13].…”
Section: Introductionmentioning
confidence: 99%